2023
DOI: 10.3390/ijms24076825
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Aqueous Humor Proteome Predicts Metastatic Potential in Uveal Melanoma

Abstract: Gene expression profiling (GEP) is clinically validated to stratify the risk of metastasis by assigning uveal melanoma (UM) patients to two highly prognostic molecular classes: class 1 (low metastatic risk) and class 2 (high metastatic risk). However, GEP requires intraocular tumor biopsy, which is limited by small tumor size and tumor heterogeneity; furthermore, there are small risks of retinal hemorrhage, bleeding, or tumor dissemination. Thus, ocular liquid biopsy has emerged as a less-invasive alternative.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In a recent vitreous study of UM [20], a large number of proteins (n = 1000) was evaluated in relation to GEP classes in a discovery sample comprising 8 UM subjects, and even though the 20 proteins selected for follow-up in 11 UM subjects did not include our cytokines of interest, the study results similarly suggested the prognostic potential of vitreous protein profiling. In two recent UM studies, which evaluated aqueous humor proteins in relation to GEP classes (for 1469 proteins) [36] or as related to clinicopathological and cytogenetic prognosticators (for 84 proteins) [38], the study results similarly suggested the potential of aqueous humor protein profiling to differentiate between different prognostic categories. Aqueous humor molecular profiles appear to be primarily influenced by the ciliary body involvement in UM, probably because of the close anatomic relationship between the aqueous humor and the ciliary body [18,38].…”
Section: Vitreous Cytokines Differentially Expressed In Eyes With Cms...mentioning
confidence: 85%
See 2 more Smart Citations
“…In a recent vitreous study of UM [20], a large number of proteins (n = 1000) was evaluated in relation to GEP classes in a discovery sample comprising 8 UM subjects, and even though the 20 proteins selected for follow-up in 11 UM subjects did not include our cytokines of interest, the study results similarly suggested the prognostic potential of vitreous protein profiling. In two recent UM studies, which evaluated aqueous humor proteins in relation to GEP classes (for 1469 proteins) [36] or as related to clinicopathological and cytogenetic prognosticators (for 84 proteins) [38], the study results similarly suggested the potential of aqueous humor protein profiling to differentiate between different prognostic categories. Aqueous humor molecular profiles appear to be primarily influenced by the ciliary body involvement in UM, probably because of the close anatomic relationship between the aqueous humor and the ciliary body [18,38].…”
Section: Vitreous Cytokines Differentially Expressed In Eyes With Cms...mentioning
confidence: 85%
“…These biological processes are mediated by interactions among various cellular and soluble components of the TME, ultimately leading to either a pro-tumorigenic (growth and spread) or anti-tumorigenic (regression) outcome in UM [3,[21][22][23][24][25][26]. Given the growing interest in using less invasive and more advantageous liquid biopsy-based approaches to study and manage solid cancers, the protein markers (including inflammatory mediators and angiogenic factors) have also been increasingly investigated in ocular fluids of UM-affected eyes in recent years [3,4,20,25,26,[32][33][34][35][36][37][38][39]. While both aqueous and vitreous humor have been used for this purpose (obtained in vivo or ex vivo from the eyes undergoing eye-preserving therapy or enucleation surgery), the data on vitreous remain limited due to fewer studies that focused on this ocular fluid by statistically analyzing either a selected set of cytokines (<30 analytes) [3,25,26] or a small discovery cohort (<10 UM samples) for a large number of proteins [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to vitreous liquid biopsies, recent studies demonstrated that the AH proteome is valuable to distinguish between low and high metastatic risk of patients with uveal melanoma. ,, AH liquid biopsies are even more accessible, can be performed in a variety of clinical settings including outpatient clinics, and are repeatable allowing for individualized surveillance strategies after tumor treatment …”
Section: Aqueous Humor Liquid Biopsy Proteomicsmentioning
confidence: 99%
“…Novel affinity proteomics discovery platforms, such as SomaScan 11k and Olink Explore HT, enable the analysis of thousands of protein targets in a semi-quantitative manner—without any sample pre-processing. While being largely developed for the analysis of blood-derived samples, the platforms offer access to sample matrices beyond those, including saliva ( Scholtz et al, 2020 ), urine ( Daza et al, 2023 ), ascites ( Finkernagel et al, 2019 ) and many other bodily fluids including AH and vitreous humor (VH) ( Lamy et al, 2020 ; Peng et al, 2023 ; Wolf et al, 2023 ).…”
Section: Deciphering the Ah Proteomementioning
confidence: 99%